2004
DOI: 10.1016/j.cellbi.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analyses and studies on the nuclear DNA content in 30 genotypes of potato (Solanum tuberosum) L.

Abstract: The cytophotometric estimation of 4C DNA content, and karyotypic and somatic chromosome number analyses were carried out in 30 genotypes comprising seven cultivars and 23 advanced breeding lines of Solanum tuberosum. Detailed karyotype analysis revealed genotype specific chromosomal characteristics and structural alterations in chromosomes of the genome, with a rare phenomenon of aneusomatic (2n = 4x + 2 = 50) condition in cv.K. Chandramukhi. The origin of this variation could be attributed to mitotic non-disj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Using pachytene analysis of haploids, Yeh and Peloquin (1965) found no gross structural differences between haploids of the groups Tuberosum and Andigena. However, recent karyotypic analyses and studies on the nuclear DNA content showed that highly significant variations were observed in the genome length, volume and total form percentage at the cultivar level in 30 genotypes of cultivated potato (Mohanty et al 2004). In the present study, karyotypic analysis of diploid Mexican S. pinnatisectum and tetraploid S. tuberosum for the number of metacentric and telocentric chromosomes demonstrated that, although most of the chromosomes were morphologically similar, there were large structural differences between these 2 species.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Using pachytene analysis of haploids, Yeh and Peloquin (1965) found no gross structural differences between haploids of the groups Tuberosum and Andigena. However, recent karyotypic analyses and studies on the nuclear DNA content showed that highly significant variations were observed in the genome length, volume and total form percentage at the cultivar level in 30 genotypes of cultivated potato (Mohanty et al 2004). In the present study, karyotypic analysis of diploid Mexican S. pinnatisectum and tetraploid S. tuberosum for the number of metacentric and telocentric chromosomes demonstrated that, although most of the chromosomes were morphologically similar, there were large structural differences between these 2 species.…”
Section: Discussionmentioning
confidence: 76%
“…Identification of the potato chromosomes based on their length, centromeric position, arm ratio, and morphological characteristics is possible at mitosis using the present technique. There has been no detailed karyotype studies published for diploid Mexican species S. pinnatisectum, although some preliminary karyotype of dihaploid and tetraploid cultivated potato had been analysed (Yeh and Peloquin 1965, Visser et al 1988, Mohanty et al 2004. Using pachytene analysis of haploids, Yeh and Peloquin (1965) found no gross structural differences between haploids of the groups Tuberosum and Andigena.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mohanty et al [15] identificaron alteraciones estructurales en cromosomas produciendo un fenómeno raro de aneugénesis (2n = 4xC2 = 50). Esta variación fue atribuida a la no disyunción mitótica de los tallos, dando origen a raíces aneusomáticas, sin embargo, se pudo confirmar que estas accesiones contaban con una dotación cromosómica de 48 y 24 cromosomas perteneciendo al grupo andigenum (Tabla II).…”
Section: Análisis Citogenéticounclassified